2012
DOI: 10.1007/s12263-012-0308-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomics-based personalised nutritional advice: in search of a business model?

Abstract: Nutritional advice has mainly focused on population-level recommendations. Recent developments in nutrition, communication, and marketing sciences have enabled potential deviations from this dominant business model in the direction of personalisation of nutrition advice. Such personalisation efforts can take on many forms, but these have in common that they can only be effective if they are supported by a viable business model. The present paper takes an inventory of approaches to personalised nutrition curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 22 publications
1
41
0
2
Order By: Relevance
“…It was appropriate to conduct this survey on-line given that most available personalised nutrition services are delivered, at least in part, by means of internet technology (Ronteltap et al, 2012). The response rate for this study, although similar to that found by other online surveys (e.g.…”
Section: Insert Figure 1 Heresupporting
confidence: 69%
“…It was appropriate to conduct this survey on-line given that most available personalised nutrition services are delivered, at least in part, by means of internet technology (Ronteltap et al, 2012). The response rate for this study, although similar to that found by other online surveys (e.g.…”
Section: Insert Figure 1 Heresupporting
confidence: 69%
“…Over the last decade, a substantial number of Internet companies have offered personalized information based upon individual DNA (Ronteltap et al 2012). Not all of these companies offer health-related information.…”
Section: Personalized Nutrition Services On the Internetmentioning
confidence: 99%
“…At the same time, although business models for personalized nutrition offerings are still, by and large, under development, current Internet services (Ronteltap et al 2012) already appear to reveal a need to further guaranty legal certainty by ensuring privacy and the highest standards of consumer protection and safety. Three steps in delivering personalized nutrition products particularly require attention from a legal perspective: (1) gathering personal information from the consumer; (2) using the consumer's data to (automatically) generate personalized nutrition advice based on validated algorithms; and (3) providing advice to the consumer.…”
Section: Legal Aspects Of Personalized Nutritionmentioning
confidence: 99%
“…delivered at varying levels where one level builds on the foundations of another (8) . Within this example, a threetiered approach to personalised nutrition is taken, where level 1 personalised advice is based on assessment of the individual's diet, level 2 is based on diet and phenotypic markers such as BMI and blood markers e.g.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%